Amicus Curiae In The Criminal Evidence System In Indonesia - Cesaltina Angela Soares; I Made Agus Mahendra Iswara (Fakultas Hukum, Universitas Warmadewa, 2019)
The Criminal Procedure Code in Indonesia is not known to other parties, other than to law enforcement officers who represent victims (Investigators or Public Prosecutors), suspects (Legal advisors) and Judges. However, in civil law, there are known other parties who are interested in entering into a dispute known as intervient. The idea of a third party that has an interest in the realm of civil law is made into the forerunner of a third party in criminal procedural law in Indonesia. Against such conditions in criminal law known as the term